2022
DOI: 10.2514/1.j060961
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Finite-Volume and Spectral/hp Methods for Large-Eddy Simulation of Combustor Port Flow

Abstract: High-order accurate methods provide significant accuracy/cost benefits for well-resolved and geometrically simple scale-resolving turbulent flow simulations. However, the benefit on under-resolved unstructured grids for complex industrial geometries is unclear. The purpose of this work is to contribute to understanding of the benefit of high-order schemes for Large- Eddy Simulations (LES) in practical applications. A crucial requirement is a high-order solver that supports hybrid unstructured grids. In this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…A comparison of the performance of some of the numerical methods mentioned above is possible for some benchmark cases available in the literature. Saini et al [293] reported a comparison between the open-source codes OpenFOAM [294], based on the unstructured finite-volume method, and Nektar++, based on the spectral-hp method, for LES of a moderately complex geometry relevant to gas turbine combustor, showing better agreement with reference experimental data for Nektar++ for a given computational cost between codes or, viceversa, the same agreement could be obtained with OpenFOAM with 3.4 times more expensive simulation. Higher computational efficiency for the spectral-hp method was also demonstrated by [295] in the LES study of flow past a circular cylinder for Reynolds numbers ranging from 400 to 3900.…”
Section: Numerical Methods and Codes For Turbulent Flows Simulationsmentioning
confidence: 86%
“…A comparison of the performance of some of the numerical methods mentioned above is possible for some benchmark cases available in the literature. Saini et al [293] reported a comparison between the open-source codes OpenFOAM [294], based on the unstructured finite-volume method, and Nektar++, based on the spectral-hp method, for LES of a moderately complex geometry relevant to gas turbine combustor, showing better agreement with reference experimental data for Nektar++ for a given computational cost between codes or, viceversa, the same agreement could be obtained with OpenFOAM with 3.4 times more expensive simulation. Higher computational efficiency for the spectral-hp method was also demonstrated by [295] in the LES study of flow past a circular cylinder for Reynolds numbers ranging from 400 to 3900.…”
Section: Numerical Methods and Codes For Turbulent Flows Simulationsmentioning
confidence: 86%